Maf1 Ameliorates Sepsis-Associated Encephalopathy by Suppressing the NF-kB/NLRP3 Inflammasome Signaling Pathway - Chen, Shenglong; Tang, Chaogang; Ding, Hongguang; Wang, Zhonghua; Liu, Xinqiang; Chai, Yunfei; Jiang, Wenqiang; Han, Yongli; Zeng, Hongke (Frontiers in Immunology, 2020)
Background: The NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome has been identified as an important mediator of blood-brain-barrier disruption insepsis-associated encephalopathy (SAE). However, no information is available concerning the critical upstream regulators of SAE. Methods: Lipopolysaccharide (LPS) were used to establish an in vitro model of blood-brain barrier (BBB) disruption and an in vivo model of SAE. Disruption of BBB integrity was assessed by measuring the expression levels of tight-junction proteins. NLRP3 inflammasome activation, pro-inflammatory cytokines levels, and neuroapoptosis were measured using biochemical assays. Finally, the FITC-dextran Transwell assay and Evan's blue dye assay were used to assess the effect of Maf1 on LPS-induced endothelial permeability in vitro and in vivo. Results: We found that Maf1 significantly suppressed the brain inflammatory response and neuroapoptosis induced by LPS in vivo and in vitro. Notably, Maf1 downregulated activation of the NF-κB/p65-induced NLRP3 inflammasome and the expression of pro-inflammatory cytokines. In addition, we found that Maf1 and p65 directly bound to the NLRP3 gene promoter region and competitively regulated the function of NLRP3 in inflammations. Moreover, overexpression of NLRP3 reversed the effects of p65 on BBB integrity, apoptosis, and inflammation in response to LPS. Our study revealed novel role for Maf1 in regulating NF-κB-mediated inflammasome formation, which plays a prominent role in SAE. Conclusions: Regulation of Maf1 might be a therapeutic strategy for SAE and other neurodegenerative diseases associated with inflammation.